Hanging Together or Being Hung Separately: The Strategic Power of Coalitions where Bargaining Occurs with Incomplete Information - Kai A. Konrad; Thomas R. Cusack (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
What is the strategic role of membership in an intergovernmental group with unanimity requirements if the group negotiates with an external player in a setting with incomplete information? Being in such a group has a strategic effect compared to negotiating as a standalone player and reduces the demands of the outside player: being in a group lends additional bargaining power. Negotiating as a group may also cause more inefficiencies due to bargaining failure, and this may harm also the intergovernmental group. We uncover the role of preference alignment and preference independence between members of the coalition group for equilibrium payoffs and welfare effects. In this analysis we also distinguishing between coalition groups with and without side payments. Overall, coalition groups tend to perform well for the members of the coalition group in comparison to fully decentralized negotiations, particularly if the objectives of the members of the coalition group are not always perfectly aligned.
Keywords: F51; F53; F59; 330